Surveilans Kesehatan Remaja: Skrining Manual Tanda Gejala dan Pemeriksaan Fisik untuk Deteksi Anemia di Lingkungan Sekolah Kota Palembang - Intan Kumalasari; Neina Messy Agustin; Suci Nurinda; Balkis Syalshalisa; Raya Syakilla Eleuwarin; Dea Silvia; Marshella Rui Utami (Lembaga Pengembangan Kinerja Dosen, 2026)
Anemia in adolescents is a serious health issue that impacts students' concentration and productivity. This community service activity aims to conduct early detection of anemia through a comprehensive manual screening method at three high schools: SMA Sains Alumnika Palembang, SMA Candradimuka, and SMA Mandiri. The implementation method involved three main stages: identification of clinical signs and symptoms (5L), visual observation of the palpebral conjunctiva, and hemoglobin (Hb) level measurement using Point of Care Testing (POCT) devices. Held from April 1st to 8th, 2026, the activity involved the active participation of students and school authorities as an effort toward independent nutritional surveillance. The screening results showed a correlation between subjective symptoms, pale conjunctiva conditions, and Hb measurement results in the field. Changes in students' behavior regarding nutritional intake and the emergence of new awareness among school authorities about the importance of routine check-ups served as indicators of successful social transformation. In conclusion, integrated manual screening is highly effective as a preventive health measure for adolescents within educational environments.